Factors influencing adoption of facility-assisted delivery - a qualitative study of women and other stakeholders in a Maasai community in Ngorongoro District, Tanzania - Paul D. Mosley; Kisiaya Saruni; Bernadetha Lenga (BMC, 2020)
Abstract Background Tanzania's One Plan II health sector program aims to increase facility deliveries from 50 to 80% from 2015 to 2020. Success is uneven among certain Maasai pastoralist women in Northern Tanzania who robustly prefer home births to facility births even after completing 4+ ANC visits. Ebiotishu Oondomonok Ongera (EbOO) is a program in Nainokanoka ward to promote facility births through a care-group model using trained traditional birth attendants (TBAs) as facilitators. Results to date are promising but show a consistent gap between women completing ANC and those going to a facility for delivery. A qualitative study was conducted to understand psychosocial preferences, agency for decision-making, and access barriers that influence where a woman in the ward will deliver. Methods In-depth interviews, focus group discussions and key-informant interviews were conducted with 24 pregnant and/or parous women, 24 TBAs, 3 nurse midwives at 3 health facilities, and 24 married men, living in Nainokanoka ward. Interviews and discussions were transcribed, translated, and analyzed thematically using a grounded theory approach. Results Most women interviewed expressed preference for a home birth with a TBA and even those who expressed agency and preference for a facility birth usually had their last delivery at home attributed to unexpected labor. TBAs are engaged by husbands and play a significant influential role in deciding place of delivery. TBAs report support for facility deliveries but in practice use them as a last resort, and a significant trust gap was documented based on a bad experience at a facility where women in labor were turned away. Conclusions EbOO project data and study results show a slow but steady change in norms around delivery preference in Nainokanoka ward. Gaps between expressed intention and practice, especially around 'unexpected labor' present opportunities to accelerate this process by promoting birth plans and perhaps constructing a maternity waiting house in the ward. Rebuilding trust between facility midwives, TBAs, and the community on the availability of health facility services, and increased sensitivity to women's cultural preferences, could also close the gap between the number of women who are currently using facilities for ANC and those returning for delivery.